Population‐specific modelling of between/within‐subject flow variability in the carotid arteries of the elderly - Lassila, Toni; Sarrami‐Foroushani, Ali; Hejazi, SeyedMostafa; Frangi, Alejandro F. (International journal for numerical methods in biomedical engineering, 2020)
Computational fluid dynamics models are increasingly proposed for assisting the diagnosis and management of vascular diseases. Ideally, patient‐specific flow measurements are used to impose flow boundary conditions. When patient‐specific flow measurements are unavailable, mean values of flow measurements across small cohorts are used as normative values. In reality, both the between‐subjects and within‐subject flow variabilities are large. Consequently, neither one‐shot flow measurements nor mean values across a cohort are truly indicative of the flow regime in a given person. We develop models for both the between‐subjects and within‐subject variability of internal carotid flow. A log‐linear mixed effects model is combined with a Gaussian process to model the between‐subjects flow variability, while a lumped parameter model of cerebral autoregulation is used to model the within‐subject flow variability in response to heart rate and blood pressure changes. The model parameters are identified from carotid ultrasound measurements in a cohort of 103 elderly volunteers. We use the models to study intracranial aneurysm flow in 54 subjects under rest and exercise and conclude that OSI, a common wall shear‐stress derived quantity in vascular CFD studies, may be too sensitive to flow fluctuations to be a reliable biomarker. This paper develops statistical models for between and within‐subject flow variability in the carotid arteries of elderly people. Gaussian process models are used to model between‐subject variability, and a cerebral autoregulation model is used to model within‐subject variability. We use the models to study the flow‐induced variability of WSS in intracranial aneurysms and find that certain WSS indicators are less sensitive to physiological fluctuations than others.